Case Series: Upper Airway Obstruction in Post-Acute Sequelae of Covid-19 (Pasc) Infection Due to Subglottic Stenosis - Rizki, Niken Ageng; Mushahigo, Mushahigo; Santjoko, Mikael Fernando (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2022)
Introduction: Post-Acute Sequelae of Covid-19 (PASC) manifestations can lead to upper airway obstruction, especially in patients with a history of intubation. Tracheal intubation can cause damage to the subglottic, the lowest part of the larynx; SARS-CoV-2 infection damages not only the pulmonary system but also the trachea. Subglottic stenosis is an abnormality in the form of narrowing of the airway in the subglottic area. This case series demonstrates that subglottic stenosis needs to be broadly understood as it contributes to PASC and should be considered an airway emergency. Objective: To emphasize the symptoms and signs of subglottic stenosis in patients with prolonged intubation and to show the correlation between the respiratory tract symptoms and factors contributing to airway obstruction. Case: We present 2 cases, one month after discharge from the hospital; a 55-year-old man and a 32-year-old man. both came with stridor, dyspnoea, intercostal retractions one month after being hospitalized due to covid-19 infection Conclusion: There are many symptoms and signs that may occur with shortness of breath, making diagnosis difficult. It is necessary to conduct investigations to establish the diagnosis and find the cause of shortness of breath. Early tracheostomy shortens days on the ventilator, intensive care unit, and hospital and should be considered for patients in the intensive care unit at risk for more than seven days of intubation.